Atención al cliente en la Notaría Segunda del cantón Babahoyo, en el periodo 2023. - Collahuazo Castro, Melissa Thalía (2024)
This case study analyzes customer service at the Second Notary of the Babahoyo Canton, focusing on improving the user experience, since customer satisfaction depends largely on how they evaluate the service received, customer orientation implies that all Staff actions must focus on satisfying user needs, and service quality is essential to retain customers, given that attracting new ones is more expensive. Staff behavior is key to quality service; employees must listen and respond to customer complaints with empathy and promptness, which improves customer satisfaction. Furthermore, employees' job satisfaction influences their productivity and service quality. Consistent and proper training of staff is crucial to ensure they can perform their duties efficiently and improve customer service. Infrastructure and logistics also play an important role in service quality. A modern, well-designed infrastructure can streamline processes and improve the customer experience. However, this needs to be complemented with well-trained staff and efficient operational processes. In the methodological context, a mixed approach with surveys and interviews was used to collect data from clients and the notary, thus identifying the causes of dissatisfaction and proposing improvements. The research was based on qualitative and quantitative methods, combining descriptive and analytical data to provide a complete analysis of the notary's situation.